Empowering Saudi Women through Automobile Advertisements: A Transitivity Analysis - Alsaedi, Najah (International Journal of Language and Literary Studies, 2024)
The purpose of the present study is to examine automobile advertisements that specifically targeted Saudi women during the year the ban on women driving was lifted. The study employed a critical discourse analysis (CDA) focusing on Halliday's transitivity system to identify the transitivity processes of automobile advertisements. To discern the transitivity processes used, a combination of qualitative and quantitative methods were utilized to attain a comprehensive understanding of the various types of transitivity processes and the identifying themes promoted by these processes. The findings reveal that the material process was the most frequent process used in automobile advertisements targeting Saudi women, followed by the existential and relational processes. In addition, these processes were mainly employed to empower Saudi women, which is the primary theme identified during the qualitative analysis. Examining the roles and circumstances of the participants could yield more relevant data for future research.